Can the BRICS Games replace the Olympics? - Shvetsov, A. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The purpose of this work is to study the results of the participation of Russian athletes in the V BRICS Games,aswell as to assess the contribution of these competitions to the formation of an alternative model of international sporting events.